2019
DOI: 10.7554/elife.44667
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte morphogenesis is dependent on BDNF signaling via astrocytic TrkB.T1

Abstract: Brain-derived neurotrophic factor (BDNF) is a critical growth factor involved in the maturation of the CNS, including neuronal morphology and synapse refinement. Herein, we demonstrate astrocytes express high levels of BDNF’s receptor, TrkB (in the top 20 of protein-coding transcripts), with nearly exclusive expression of the truncated isoform, TrkB.T1, which peaks in expression during astrocyte morphological maturation. Using a novel culture paradigm, we show that astrocyte morphological complexity is increas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 71 publications
13
91
0
Order By: Relevance
“…Given the close relationship between astrocyte processes and synapses, it is not surprising that neurons or neuronal activity or both participate in astrocyte morphogenesis and PAP plasticity 41,[72][73][74][75][76][77][78][79][80][81][82] . Previous studies demonstrated that astrocytes exhibit reduced territory and neuropil infiltration in dark-reared animals, providing evidence for the involvement of neuronal activity in astrocyte morphogenesis 73,74 .…”
Section: Morphological Maturationmentioning
confidence: 99%
“…Given the close relationship between astrocyte processes and synapses, it is not surprising that neurons or neuronal activity or both participate in astrocyte morphogenesis and PAP plasticity 41,[72][73][74][75][76][77][78][79][80][81][82] . Previous studies demonstrated that astrocytes exhibit reduced territory and neuropil infiltration in dark-reared animals, providing evidence for the involvement of neuronal activity in astrocyte morphogenesis 73,74 .…”
Section: Morphological Maturationmentioning
confidence: 99%
“…5n). Astrocyte functional genes were also significantly decreased in SOX2-defciency mice, for example, glutamate transport genes Slc1a2 and Slc1a3 (38), synaptogenesis regulatory genes Sparcl1 and Megf10 (21,39), astrocytic morphogenesis-promoting gene Ntrk2 (35), and K + -buffering gene Kcnj10 (28) ( Fig. 5n).…”
Section: Sox2 Targets a Cohort Of Genes That Are Crucial For Astrocytmentioning
confidence: 89%
“…In addition, SOX2 also bound to other characteristic astrocyte genes, for example, Gfap, Apq4, Wnt7a, Ntrk2, and Sparcl1 ( Fig. 5g-l), among which Ntrk2 has been shown to promote astrocyte morphological maturation both in vivo and in in vitro (35).…”
Section: Sox2 Targets a Cohort Of Genes That Are Crucial For Astrocytmentioning
confidence: 98%
“…Therefore, it may be anticipated that the observed neurodevelopmental effects of STEE in this study were mediated by the activation of TrkB and Rho signaling evident by the upregulation of their downstream effectors Pik3r1 and Limk1 , respectively ( Gupta et al, 2013 ; Tejeda and Diaz-Guerra, 2017 ; Ravindran et al, 2019 ). Particularly, recently explored role of astrocytic TrkB-T1 signaling in astrocyte morphogenesis ( Holt et al, 2019 ) warrants further research on the effect of STEE and its active compounds on TrkB activation.…”
Section: Discussionmentioning
confidence: 99%